The Considerations on a Classification Scheme for Community College Workforce Development Programs - T Miller, Michael; S. Grover, Kenda (Journal of Public Administration and Governance, 2024)
Community colleges actively engage in a broad array of pre- and in-employment workforce development programs. These programs have typically been categorized as credit or non-credit bearing, but this classification is problematic and does not account for the complexity of the type, size, or motivation for offering the program. This discussion categorizes workforce development programs based on their funding source, including federal, state, industry/private, institutional, and user based programs. This type of classification allows for a better understanding of who is being served by programs, how they might be used in the future, and ultimately, provides some foundation for program assessment.